Effect of particle size on the friction welding of Al2O3 reinforced 6160 Al alloy composite and SAE 1020 steel - Hascalik, Ahmet; Orhan, Nuri (Elsevier Sci Ltd, 2007)
The aim of this study is to investigate the feasibility of joining Al(2)O(3)reinforced Al alloy composite to SAE 1020 steel by rotational friction welding. The aluminum-based metal matrix composite (MMC) material containing 5, 10 and 15 vol% Al2O3 particles with average particle sizes of 30 and 60 mu m was produced by powder metallurgy technique. The integrity of the joints has been investigated by optical and scanning electron microscopy, while the mechanical properties assessment included microhardness and shear tests. Results indicated that Al/Al2O3 Composite could be joined to SAE 1020 steel by friction welding. However, it was pointed out that the quality of the joint was effected negatively with the increase in particle size and volume percentage of the oxide particles in the MMC. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: powder metallurgy; friction welding; particle reinforced composite